Comparative effectiveness of non-pharmacological interventions on anxiety, depression, and quality of life in patients with epilepsy: a systematic review and network meta-analysis - Haoran Luo; Xianming Ding; Junyu Zhang; Ningkun Xiao; Ningkun Xiao (Frontiers in Psychiatry)
IntroductionEpilepsy is a persistent neurological condition featuring abnormal electrical activity in the brain. Beyond its neurological symptoms, it is frequently associated with comorbid anxiety and depression, which significantly impair patients’ quality of life (QoL). Cognitive therapy (CBT), psychotherapy, and self-management (SM) have been substantiated through research to be significantly effective in alleviating psychological distress and enhancing quality of life. However, comprehensive comparisons of these diverse interventions remain scarce, highlighting a critical gap in the literature.ObjectiveThis study aims to compare, through randomized controlled trials, the effects of different non-pharmacological interventions versus controls on anxiety, depression, and quality of life in patients with epilepsy.Data sourcesA systematic search was conducted in five electronic databases: Cochrane Library, PsycInfo, PubMed, Web of Science and the Embase, covering studies published up to March 19, 2025. The search strategy included terms such as “exercise,” “mind-body exercise,” “cognitive-behavioral therapy,” “psychotherapy,” “epilepsy,” “anxiety,” “depression,” and “quality of life.”Study selectionOnly English-language randomized controlled trials (RCTs) were included. Eligible studies examined the effects of non-pharmacological interventions on anxiety, depression, and QoL in patients clinically diagnosed with epilepsy. There were no restrictions on participants’ age or gender. Control conditions included standard care, placebo, wait-list, or alternative non-pharmacological interventions.Data extraction and synthesisThree authors independently screened studies and extracted data. A frequentist random-effects network meta-analysis was conducted to calculate standardized mean differences (SMDs) along with 95% confidence intervals (CIs). The relative efficacy of interventions was ranked using the surface under the cumulative ranking curve (SUCRA). The analysis was conducted in accordance with the PRISMA-NMA reporting guidelines.Main outcomes and measuresPrimary outcomes included changes in anxiety, depression, and QoL. Outcomes were assessed using validated psychological scales across studies.ResultsFifty-eight RCTs encompassing 6,541 participants across 20 countries or regions were included. Compared to control groups(CON), enhanced education therapy (EET) and psychotherapy (PT) were significantly more effective in reducing anxiety symptoms. Psychotherapy also demonstrated notable efficacy in alleviating depressive symptoms. For QoL improvement, Cognitive-behavioral therapy (CBT), mind-body therapies (MBT), Psychotherapy (PT), and enhanced care (EC) all showed significant advantages over controls. SUCRA rankings suggested that Enhanced education therapy (EET), Psychotherapy (PT), and Enhanced care (EC) were the most effective interventions for improving anxiety, depression, and Quality of Life (QoL), respectively. Subgroup analyses further suggest that enhanced education therapy and CBT may be more beneficial for minors in reducing anxiety and improving QoL, respectively, while psychotherapy shows consistent superiority in adults for both anxiety and depression.ConclusionThis network meta-analysis of 58 RCTs highlights the comparative benefits of multiple non-pharmacological strategies in improving mental health and QoL in patients with epilepsy. Interventions such as psychotherapy, CBT, and enhanced education appear particularly effective across psychological domains. These findings support the integration of tailored, non-pharmacological approaches into routine care for epilepsy and underscore the need for clinicians and policymakers to prioritize mental health alongside seizure control.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD420251015149.